3D Analysis of Facial Morphology of a Colombian Population Compared to Adult Caucasians - Bravo-Hammett, Sonia; Nucci, Ludovica; Christou, Teti; Aristizabal, Juan Fernando; Kau, Chung How (European Journal of Dentistry, 2020)
Objective: The purpose of this study involves describing the facial morphology of a Colombian population with three-dimensional (3D) imaging, and comparing their facial morphology with the Caucasian to create a database for this ethnicity.Materials and Methods: The study, which included 135 subjects selected from the Valle University in Cali, Colombia, and 535 Caucasian subjects selected from the FaceBase–Data (1U01DE024449–01), was funded by the National Institute of Dental and Craniofacial Research. All images were taken in the natural head position (NHP) and captured using a stereo-photogrammetric camera system (3dMDface) to obtain a 3D image of each patient. The subjects were between 19 to 31 years of age, with a normal body mass index (BMI), and no craniofacial deformities. All images were plotted and analyzed using the 3dMDVultus software to calculate linear and angular measurements. Standard deviation (SD) and means were calculated for each measurement and analyzed using t-test for different samples.Results: The Hispanic population had wider eyes, more protruded upper and lower lips, wider face, and greater mandibular width. Caucasian females had a more acute full profile, larger middle third, and less protrusive lips. Understanding the facial morphology of different populations would help to establish a better diagnosis and treatment planning for each ethnicity.Conclusions: From this study, the following conclusions may be drawn:1. The mean values of Colombian males showed greater measurements than females in the majority of measurements.2. Caucasian females had a more acute full profile, larger middle and lower third, and less protrusive lips.3. This study showed significant ethnic differences in the linear and angular measurements, showing us the importance of considering these findings in the diagnosis and treatment planning when a Hispanic population is involved. Soft tissue values should reflect the norms according to each ethnic population in order to achieve treatment goals.
Keywords: 3D; facial morphology; 3dMD; Colombian face; Hispanic soft tissue.